1979
DOI: 10.1111/j.1365-2427.1979.tb01522.x
|View full text |Cite
|
Sign up to set email alerts
|

The rate of colonization by macro‐invertebrates on artificial substrate samplers

Abstract: The influence of exposure time upon macro-invertebrate colonization on modified Hester-Dendy substrate samplers was investigated over a 60-day period. The duration of exposure affected the number of individuals, taxa and community diversity.Tlie numbers of individuals colonizing the samplers reached a maximum after 39 days and then began to decrease, due to the emergence of adult insects. Coefficients of variation for the four replicate samples retrieved each sampling day fluctuated extensively throughout the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
2
4

Year Published

1983
1983
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 4 publications
2
24
2
4
Order By: Relevance
“…In an unstable South Island braided river, Sagar (1983) considered recolonisation of previously dry channels to be completed after 33 days in winter, and 15 days in summer. This is in contrast to the results of Meier et al (1979) in the United States, who found that diversity and number of taxa continued to increase throughout a 60-day study period. This, they suggested, occurred as new niches were created with increasing periods of exposure as a result of adult emergence and periphyton growth.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…In an unstable South Island braided river, Sagar (1983) considered recolonisation of previously dry channels to be completed after 33 days in winter, and 15 days in summer. This is in contrast to the results of Meier et al (1979) in the United States, who found that diversity and number of taxa continued to increase throughout a 60-day study period. This, they suggested, occurred as new niches were created with increasing periods of exposure as a result of adult emergence and periphyton growth.…”
Section: Discussioncontrasting
confidence: 55%
“…Additional taxa served only to decrease the percentage contribution of these two taxa and as aresult, reduced equitability. In contrast, Meier et al (1979) found that the equitability of colonisation on multiplate samplers initially decreased, butlevelled off after 24 days, as aresult of a high dominance of Chironomidae and Trichoptera species at all times. The contrasts between colonisation studies outside New Zealand and the present study reflect the fundamental characteristics of the New Zealand aquatic fauna.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Os manuais práticos de coleta de invertebrados bentônicos para biomonitoramento aconselham que os litter bags permaneçam incubados por um período de 42 a 56 dias (GIBBONS et al, 1993;APHA, 1998), porém, tem sido considerado inadequado por alguns autores (MEIER et al, 1979). Segundo Rosenberg e Resh (1982) e Mackay (1992), o tempo ideal de incubação depende do desenho amostral, da estação do ano, da localização geográfica e a medida de equilíbrio considerada.…”
Section: Análise Dos Dadosunclassified